The Spirit of Nationalism in Literature: A Case Study of Students in Yogyakarta - Anang Sudigdo; Onok Yayang Pamungkas; Hastangka; Sabar Budi Raharjo; Suprapto (Studies in Learning and Teaching, 2023)
This research is an effort to investigate the understanding of prospective student teachers in the PGSD Study Program at "AS" Universities in Yogyakarta. The focus of the research is the understanding of nationalism and the implementation of literature as a medium of nationalism. This study used quantitative methods. Research data was conducted by conducting surveys and interviews. The survey was conducted using Google Forms media. Interviews were conducted with 30 students. The results showed that students at "U.S." colleges do not all understand national identity. Of the 30 respondents, there was 1 student who did not understand the identity of the nation. However, overall they have read many books on national identity. Students also agreed that the spirit of nationalism is an important factor that every citizen must have. In addition, students agree that the values of nationalism can be taught through literature. As a form of agreement about it, they have also implemented the practice of making poems with the theme of national identity as a representation of the spirit of nationalism. The novelty of this research is that there has been no previous research that investigates the understanding of nationalism for students, especially in the field of literature in the PGSD Study Program.